Caracterização tectono-estratigráfica da sequência transicional na sub-bacia de Sergipe - Cruz, Liliane Rabêlo (2008)
This thesis deals with the tectonic-stratigraphic evolution of the Transitional Sequence in the Sergipe Sub-basin (the southern segment of the Sergipe-Alagoas Basin, Northeast Brazil), deposited in the time interval of the upper Alagoas/Aptian stage. Sequence boundaries and higher order internal sequences were identified, as well as the structures that affect or control its deposition. This integrated approach aimed to characterize the geodynamic setting and processes active during deposition of the Transitional Sequence, and its relations with the evolutionary tectonic stages recognized in the East Brazilian Margin basins. This subject addresses more general questions discussed in the literature, regarding the evolution from the Rift to the Drift stages, the expression and significance of the breakup unconformity, the relationships between sedimentation and tectonics at extensional settings, as well as the control on subsidence processes during this time interval. The tectonic-stratigraphic analysis of the Transitional Sequence was based on seismic sections and well logs, distributed along the Sergipe Sub-basin (SBSE). Geoseismic sections and seismic facies analysis, stratigraphic profiles and sections, were compiled through the main structural blocks of this sub-basin. These products support the depositional and tectonic-stratigraphic evolutionary models built for this sequence. The structural analysis highlighted similarities in deformation styles and kinematics during deposition of the Rift and Transitional sequences, pointing to continuing lithospheric extensional processes along a NW trend (X strain axis) until the end of deposition of the latter sequence was finished by the end of late Aptian. The late stage of extension/rifting was marked by (i) continuous (or as pulses) fault activity along the basin, controling subsidence and creation of depositional space, thereby characterizing upper crustal thinning and (ii) sagstyle deposition of the Transitional Sequence at a larger scale, reflecting the ductile stretching and thinnning of lower and sub crustal layers combined with an increasing importance of the thermal subsidence regime. Besides the late increments of rift tectonics, the Transitional Sequence is also affected by reactivation of the border faults of SBSE, during and after deposition of the Riachuelo Formation (lower section of the Transgressive Marine Sequence, of Albian age). It is possible that this reactivation reflects (through stress propagation along the newlycreated continental margin) the rifting processes still active further north, between the Alagoas Sub-basin and the Pernambuco-Paraíba Basin. The evaporitic beds of the Transitional Sequence contributed to the development of post-rift structures related to halokinesis and the continental margin collapse, affecting strata of the overlying marine sequences during the Middle Albian to the Maastrichtian, or even the Paleogene time interval. The stratigraphic analysis evidenced 5 depositional sequences of higher order, whose vertical succession indicates an upward increase of the base level, marked by deposition of continental siliciclastic systems overlain by lagunar-evaporitic and restricted marine systems, indicating that the Transitional Sequence was deposited during relative increase of the eustatic sea level. At a 2nd order cycle, the Transitional Sequence may represent the initial deposition of a Transgressive Systems Tract, whose passage to a Marine Transgressive Sequence would also be marked by the drowning of the depositional systems. At a 3rd order cycle, the sequence boundary corresponds to a local unconformity that laterally grades to a widespread correlative conformity. This boundary surface corresponds to a breakup unconformity , being equivalent to the Pre-Albian Unconformity at the SBSE and contrasting with the outstanding Pre-upper Alagoas Unconformity at the base of the Transitional Sequence; the latter is alternatively referred, in the literature, as the breakup unconformity. This Thesis supports the Pre-Albian Unconformity as marker of a major change in the (Rift-Drift) depositional and tectonic setting at SBSE, with equivalent but also diachronous boundary surfaces in other basins of the Atlantic margin. The Pre-upper Alagoas Unconformity developed due to astenosphere uplift (heating under high lithospheric extension rates) and post-dates the last major fault pulse and subsequent extensive block erosion. Later on, the number and net slip of active faults significantly decrease. At deep to ultra deep water basin segments, seaward-dipping reflectors (SDRs) are unconformably overlain by the seismic horizons correlated to the Transitional Sequence. The SDRs volcanic rocks overly (at least in part) continental crust and are tentatively ascribed to melting by adiabatic decompression of the rising astenospheric mantle. Even though being a major feature of SBSE (and possibly of other basins), the Pre-upper Alagoas Unconformity do not correspond to the end of lithospheric extension processes and beginning of seafloor spreading, as shown by the crustal-scale extensional structures that post-date the Transitional Sequence. Based on this whole context, deposition of the Transitional Sequence is better placed at a late interval of the Rift Stage, with the advance of an epicontinental sea over a crustal segment still undergoing extension. Along this segment, sedimentation was controled by a combination of thermal and mechanical subsidence. In continuation, the creation of oceanic lithosphere led to a decline in the mechanical subsidence component, extension was transferred to the mesoceanic ridge and the newly-formed continental margin (and the corresponding Marine Sequence) began to be controlled exclusively by the thermal subsidence component. Classical concepts, multidisciplinary data and new architectural and evolutionary crustal models can be reconciled and better understood under these lines